New growth platform framework for Swiss acute hospitals; an empirical study for the development of dynamic capabilities - Alimpic, Zoran (Serbian Journal of Management, 2013)
Swiss health care is confronted with fundamental changes. On the one hand, there are increasing costs in patient treatments, caused by innovative technology with new high-capacity medical devices, and a lack of effectiveness and efficiency in the organisation of a hospital. On the other hand, hospitals do have decreasing revenues with the introduction of the new patient classification and tariff system DRG (Diagnosis Related Groups) by 2012. For every DRG, hospitals will receive a fixed price, separate from the actual costs of the patient treatment. In this paper it was explored the case of 13 successful Swiss private acute hospitals which are also confronted with these pressures to reduce their costs of patient treatment and therefore to optimise their processes of care. This research focuses on dynamic capabilitie of the hospitals. The research is started with the evaluation of new trends, key customers’ needs, and capabilities, with questionnaires for attending physicians and hospital managers. The NGP approach gives hospital managers the enough crucial information for a strategy formulation in fundamental changing environments, which is the key contribution of this manuscript.